Social Determinants of Health: The Fifth Vital Sign - Pardo, Christina; McLaren, Rodney, Jr.; Minkoff, Howard (American Journal of Perinatology, 2022)
Introduction Since the last decade, social determinants of health (SDOH) have become a vital component of the liturgy of public health. From that time, the number of articles on SDOH cited in PubMed has increased from approximately 775 to over 4,700.Issue In obstetrics, social determinants of health have particular resonance in discussions of maternal mortality and health disparities and the number of articles on SDOH in obstetrics has increased sixfold during the same interval. However, while most obstetricians are now aware of SDOH, many are unsure about how to address them within the context of their own practice.Summary In this piece, we will discuss the importance of SDOH in obstetrics, the reasons why most obstetricians have not engaged with it and suggest steps to help bridge the gap between merely accepting SDOH's importance and implementing strategies to mitigate their effects.Key Points
Keywords: health disparities; public health; social determinants of health; social disadvantage